The Moon is Flicts: Political and Queer Uses of Negativity in a Brazilian Picturebook* - Santos, Elisa Melo Franco (FRAME, Journal of Literary Studies, 2026)
This article presents a queer reading of Flicts (1969), the first fully-colored picturebook printed in Brazil, published in the worst phase of the military dictatorship that ruled the country from 1964 to 1985. In conversation with queer aesthetics of negativity, it investigates how the picturebook deals with difficult themes––such as inclusion, exclusion and exile––through its employment of negative affects, and how Flicts can represent a discourse of dissent from the hegemonic vision of its social and political context. By weaving together textual and visual analyses, I propose that affects such as failure, isolation and withdrawal in Flicts become a tool for political criticism.